Funding, competition and the efficiency of NGOs: an empirical analysis of non-charitable expenditure of US NGOs engaged in foreign aid - Nunnenkamp, Peter; Öhler, Hannes (Kyklos, 2012)
We assess the determinants of the wide variation in the efficiency of foreign aid activities across US-based non-governmental organizations (NGOs). In particular, we analyze whether non-charitable expenditures for administration, management and fundraising depend on the intensity of competition among NGOs and on the degree to which they are refinanced by governments. We control for NGO heterogeneity in various dimensions as well as major characteristics of recipient countries. We find that fiercer competition is associated with more efficient foreign aid activities of NGOs, rather than leading to “excessive” fundraising. Official funding tends to increase administrative costs. Nevertheless, officially financed NGOs spend relatively more on charitable activities since they are less concerned with collecting private donations through fundraising efforts.